Taking the high road a metropolitan agenda for transportation reform - Katz, Bruce; Puentes, Robert; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2005)
"Examines the challenges facing U.S. cities, suburbs, and metropolitan areas in light of the national debate on transportation policy--including finance, decisionmaking, access for the elderly and working poor, and congestion--and provides reform options that speak to leaders at the state, metropolitan, and local levels"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Urban transportation policy -- United States; Transportation and state -- United States; Electronic books